Upswing in the world economy - Günter Großer; Günter Weinert (Intereconomics, 1995)
The world economy gained distinct momentum last year. Following North America, the forces for growth have now prevailed in Western Europe and the Japanese economy has also picked up. Real gross domestic product in the industrial countries rose faster than expected at 3%. Will this upward trend keep going, as it must to alleviate unemployment?
Keywords: 330; Economic Trends